Program Gerakan Literasi Sekolah Dan Dinamika Pelaksanaannya Di SMA Negeri 1 Basa Ampek Balai Tapan Kabupaten Pesisir Selatan - Jayandri Jayandri; Nurizzati Nurizzati (JURNAL PENDIDIKAN ROKANIA, 2023)
The objectives of this study are (1) to describe the implementation of the GLS program, (2) to describe the supporting and inhibiting factors of the GLS program, (3) to describe the contribution of school libraries in the implementation of the GLS. The type of research used is descriptive research with a qualitative approach. Informants in this study used purposive sampling technique. Informants in this study there are 5 informants consisting of the principal, the head of the library, teachers, and 2 students. Data collection techniques using observation, interviews and documentation. The data analysis technique was carried out with the stages of data reduction, data presentation and drawing conclusions. The results of this study are as follows. (1) SMA Negeri 1 Basa Ampek Balai Tapan has implemented GLS since 2019, namely 15 minutes of reading, reading area, reading garden, and the most diligent library visitors. (2) Supporting factors for the implementation of the GLS are the active role of all school members, school funds, collaboration with donors and support from students' parents. And the inhibiting factor for implementing GLS is the influence of technology such as the negative influence of gadgets, students prefer to play gadgets than go to the library. Efforts made to overcome these problems are the cooperation of all elements of the school to encourage students so that students are enthusiastic and active in literacy activities. (3) The contribution of the school library in implementing the school literacy movement program is the first to procure collections in the library, the second is library services, the third is library collaboration, the fourth is appreciation for users, the fifth is library promotion and the sixth is the school library program